Miss Jamaica Gail Phillips, Thelma Campbell and Yvon - Austin Ferguson
A photo of Miss Jamaica Gail Phillips, Thelma Campbell and Yvon.
Daily News Collection, Level 1 photograph.
Special Collection Floor.
Keywords: Phillips, Gail -- Photographs. -- Jamaica; Photographs